Pengembangan Modul Praktikum Mata Kuliah Perbaikan Dan Perawatan Peralatan Audio Video Elektronika Pada Jurusan Pendidikan Teknik Elektronika FT-UNM - Sutarsi Suhaeb (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is (1) to learn how to develop a practicum module in the repair and maintenance of audio video equipment in the department of electronics engineering education (2) to find out the module practicum repair and maintenance of audio video equipment provided can be used practically and effectively in the electronics engineering education department. The type of research used is research and development which aims to develop and produce products. The development procedure discusses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Research subjects are students of the electronics engineering education department FT-UNM, while the research object is the practicum module. The research instrument uses report sheets according to two material experts, two design experts, two observers and student responses. The results of the trial in this study is an analysis of the results of the validation of two material experts, the percentage percentage of the total yield of 93% with the category